PROFIL KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS KELAS IV SDN WIROWONGSO 02 JEMBER - Imroatul Hasanah; Mely Agustin Reni Pitasari; Muhammad Ilyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the critical thinking skills of fourth-grade students in classes IV A and IV B at SDN Wirowongso 02 in science learning, particularly on the topic of force. The research employed a descriptive qualitative approach with data collection techniques consisting of written tests and interviews. The written test comprised ten essay questions developed based on Ennis’s critical thinking indicators, while interviews were conducted with classroom teachers as supporting data to gain deeper insight into the implementation of science learning at the school. The results indicate that students’ critical thinking skills in both classes vary across indicators. The indicators of elementary clarification and basic support fall into the moderate category, suggesting that students are generally able to understand problems and provide answers with simple reasoning. However, the indicators of inference, advanced clarification, as well as strategy and tactics remain in the low category. This finding shows that students still experience difficulties in drawing in-depth conclusions, developing advanced explanations, and formulating appropriate problem-solving strategies. These results emphasize the need for more varied, interactive, and context-based science learning practices in elementary schools to enhance students’ critical thinking skills. Furthermore, the role of teachers in creating a supportive learning environment, encouraging active discussion, and fostering students’ learning motivation is crucial for improving the critical thinking skills of students in classes IV A and IV B.